Analisis Kemitraan dan Potensi Ekonomi terhadap peningkatan pendapatan Petani Kopi - Zubair, Ahmad; Suherman , Suherman; Darmawan, Darmawan (Jurnal Ilmiah Pertanian dan Peternakan, 2024)
Purpose: This study aimed to determine (1) the income potential of partnered and non-partnered coffee farmers and (2) the factors that affect the income of partnered coffee farmers in Baroko District, Enrekang Regency. Methodology: This research used both qualitative and quantitative methods. Data were obtained through observation, interviews, and documentation. The population consisted of all partnered and non-partnered coffee farmers in the Baroko District. A total of 80 respondents were selected using purposive sampling. Both primary and secondary data were analyzed using multiple linear regression and income analysis methods. Results: The findings revealed that the partnership model applied in Baroko District follows a general trade partnership scheme. The factors that significantly affect the income of partnered coffee farmers include production costs, production quantities, partner prices, length of partnership, and experience with the partner. In contrast, variables such as farmer age, education level, and deferred amount did not show a significant influence on income. Conclusion: The study concludes that partnership arrangements can significantly enhance coffee farmer income when supported by appropriate cost control, stable production output, and beneficial partner pricing schemes. Non-partnered farmers tend to earn lower incomes due to less structured support and access to markets. Limitations: This study is limited to partnered and non-partnered coffee farmers in one district and used a relatively small sample. Contribution: This research provides important insights into partnership-based farming and can serve as a reference for policymakers and agricultural institutions in improving farmer income through structured cooperation models.